Comparative analysis of monetary functions in Islamic and conventional economic systems - Fatmawati, Farida (Journal of Islamic Economics Management and Business (JIEMB), 2023)
The article investigates the distinction between the functions and perceptions of money within Islamic and conventional economic systems. The purpose of the study is to elucidate the Islamic principles governing the use of money, highlighting the fundamental differences from conventional views and their implications for modern economies. The methodology employed is a qualitative approach with descriptive-analytical methods, incorporating primary sources from classical Islamic scholars and contemporary experts, as well as secondary data from relevant academic literature. The findings reveal that, unlike in conventional economics where money can be treated as a commodity, Islamic economics defines money strictly as a medium of exchange and a standard of value, not for hoarding or speculative purposes. This research underscores the necessity of adhering to Sharia principles to ensure a just and sustainable economic system. The implications suggest a re-evaluation of modern financial practices to align more closely with Islamic economic teachings, promoting ethical financial behavior and Indonesia.